Pengaruh Pertumbuhan Ekonomi Dan Inflasi Terhadap Upah Minimum Peovinsi Jawa Barat Tahun 2011-2019 - Dahlia Tsalsalaila; Harya Kuncara Wiralag; Siti Fatimah Zahra (Peneliti.net, 2022)
This study examines the relationship between economic growth and the minimum wage in West Java, the relationship between inflation and the minimum wage in West Java, and the relationship between economic growth and inflation with the minimum wage in West Java. The approach used in this research is a quantitative approach. Data collection uses secondary data by looking at the Central Statistics Agency for the province of West Java and government regulations regarding the minimum wage policy for the districts/cities of West Java province. The time series in this study is 9 years from 2011-2019 and the research object is 7 cities in West Java province. Hypothesis testing was done by using panel data regression test. The results of the study show that: (1) Economic growth has a negative and significant effect on the minimum wage of West Java province, showing a t-value of -2.890015 and a probability value of 0.0054 which is lower than 0.05. (2) Inflation has a positive and significant effect on the minimum wage of West Java province, showing a t-value of 6.538082 and a probability value of 0.0000 which is lower than 0.05. (3) Together, Economic Growth and Inflation have a significant effect on the minimum wage of West Java province, the calculated f value is 22.09883, which is greater than f table of 3.153 with a probability value of 0.000000 f-statistics, which is lower than 0.05.